Four-dimensional computed tomography analysis of bicuspid aortic valvesCentral MessagePerspective - Amine Fikani, MD; Damian Craiem, PhD; Cyrille Boulogne, PhD; Gilles Soulat, PhD; Elie Mousseaux, PhD; Jerome Jouan, PhD (JTCVS Techniques)
Objectives: To evaluate the role of 4-dimensional (4D; 3-dimensional [3D] + time) analysis using multiphase cardiac computed tomography (MCCT) in the description of the aortic annulus (AA) of bicuspid aortic valves (BAV) with regard to the latest expert consensus classification. Methods: Electrocardiography-gated MCCT of 15 patients with BAV were analyzed using in-house software and compared to 15 patients with normal tricuspid aortic valve (TAV). The AA border was pinpointed on 9 reconstructed planes, and the 3D coordinates of the 18 consecutive points were interpolated in 3D using a cubic spline to calculate 3D areas, perimeters, diameters, eccentricity indexes, and global height. Measurements were repeated throughout the cardiac cycle (10 phases). Three additional planes were generated at the level of the left ventricular outflow tract (LVOT), the sinus of Valsalva, and the sinotubular junction. Results: The annulus area was significantly larger in BAV compared to TAV (mean indexed 3D area, 5.64 ± 0.84 cm2/m2 vs 4.3 ± 0.38 cm2/m2, respectively; P < .001). The AA was also larger in BAV in terms of perimeter, diameters, and height (P < .001). The Valsalva sinuses and sinotubular junction also were significantly larger in BAV compared to TAV (mean area in end-diastole, 6.06 ± 1.00 cm2 vs 4.69 ± 1.00 cm2 [P < .001] and 5.13 ± 1.62 cm2 vs 3.62 ± 0.99 cm2 [P < .001], respectively). In BAV, 3D AA shape analysis helps distinguish the 3 types of BAV: the 2-sinus type (symmetrical), the fused type, and the partial-fusion type or “form fruste” (both asymmetrical). It also allows determination of the position and height of the nonfunctional commissure. In symmetrical BAV, the nonfunctional commissure was significantly lower than the other commissures (6.01 ± 4.27 mm vs 18.24 ± 3.20 mm vs 17.15 ± 3.60 mm; P < .001), whereas in asymmetrical BAV, the 3 commissures were of comparable height (16.38 ± 0.86 mm vs 15.88 ± 1.69 mm vs 15.37 ± 0.88 mm; P = .316). There was no difference in AA eccentricity indices between TAV and BAV in all phases of the cardiac cycle; however, there was a spectrum of ellipticity for the other components of the aortic root among the different types of valves: going from TAV to asymmetrical BAV to symmetrical BAV, at end-diastole, the LVOT became more circular and the sinuses of Valsalva became more elliptical. Conclusions: 3D morphometric analysis of the BAV using MCCT allows identification of the type of BAV and the position and height of the nonfunctional commissure. There are significant differences in the morphology of the aortic root between TAV and the different types of BAV. Further studies are needed to evaluate the impact of 3D analysis on the procedural planning for pathologic BAV.